An Encounter with an Image: Humberto Rivas in Madrid, 2018–2019. Issue 1 (April 2020) - Soliman, Alia
Abstract : Alia Soliman's piece is prompted by the shock of arrest before an image taken by the Argentinian photographer Humberto Rivas. That arrest yields to the keenly felt play of memory and association, both in the moment of the photograph's immediate impact and subsequently. The result is a memoiristic piece that also works as a personal essay on time, loss, and the feeling of saudade .